Device construction for UV-C Ultraviolet Irradiation (Research, Society and Development, 2022)
During the COVID-19 pandemic, the reduction in the production and distribution of various personal protective equipment (PPE), in particular, N95 masks, emerged the need to develop a local device for disinfection of these PPE, using ultraviolet C radiation (UV-C), increasing the safety of users in case of reuse of this equipment. To accomplish this task, the UV-C irradiation system was developed and its project distributed to several institutions that expressed interest. Thus, based on the operating principles of radiotherapy equipment, which has radiation sources, accumulated dose control devices, dose rate, exposure time and safety. In March 2020, with the help of a technical and research team, it was possible to develop this device and provide the opportunity to disinfect N95 masks in case of shortage, still, as a differential, this project has a UV dose control system (mJ/cm2) in real time. However, as the University Hospital acquired PPE in sufficient quantity for its demand, the implantation of this device was not necessary. In order to enable the construction of this device, this work brings all the information necessary for its replication, allowing it to be used as a safe tool for the application of ultraviolet radiation in several areas such as the Intensive Care Unit - ICU, Materials Sterilization Center – MSC, etc.